Autoimmunity to mental health: Risk of depression in type 1 diabetes and celiac disease patients – A systematic review, meta-analysis, and bias assessment - Desalegn, Dagem; Fischer, Simone; Bedada, Yeabsira; Freuer, Dennis; Meisinger, Christa (Elsevier, 2026)
Background
Depression is expected to become the world's largest disease burden by 2030. However, the incidence of depression in individuals with Type 1 diabetes mellitus (T1DM) or Celiac disease (CD) remains poorly studied. To address this gap, a systematic review and meta-analysis was carried out.
Methods
This systematic review was approved at PROSPERO on February 9, 2025, and followed the PRISMA and MOOSE guidelines. The literature search considered all peer-reviewed quantitative studies from relevant databases up to February 7, 2025. Study-specific risk of bias was assessed using the ROBINS-E tool. Inverse variance weighted random-effects models were applied on the hazard ratio (HR) scale to pool estimates of included studies. Heterogeneity was quantified by Cochran's Q and  statistics. Sensitivity analyses consisted of influence, outlier, and subgroup analyses. E-values were calculated to assess the reliability of results regarding unmeasured confounding.
Results
Out of 17,095 articles screened, eight studies for T1DM and two for CD were included in the study. Both T1DM (HR = 2.77; 95 % CI: [1.82; 4.21]; P < 0.0001;  = 98.5 %) and CD (HR = 1.66; 95 % CI: [1.51; 1.84]; P < 0.0001;  = 35.3 %) were consistently associated with the onset of depression. Despite the high heterogeneity, which could not be fully explained for T1DM, the sensitivity analyses confirmed the results, while the E-values underscored their robustness against unmeasured confounding.
Conclusions
This meta-analysis indicates a significant increase in the incidence of depression in individuals with either T1DM or CD. Depression screening for these population is recommended. Further research is needed to clarify the underlying mechanisms for these associations.